Perioperative Airway Management Strategy and Posttransplant Successful Tracheal Resection and Reconstruction in a Heart Transplant Candidate with Post-intubation Stenosis - Ergenoglu, M. U.; Ercan, S.; Yerebakan, H.; Pektok, E.; Kucukaksu, S. (The Thoracic and Cardiovascular Surgeon, 2012)
Post-intubation tracheal stenosis (PTS) is an important clinical situation. It is estimated to occur in approximately 5% to 20% of intubated or tracheostomized patients. PTS most commonly occurs after prolonged intubation, and the treatment options have been well discussed in the literature. However, in solid organ transplantation, the necessity of administering high doses of corticosteroids as well as immunosuppressive therapies may compromise the healing processes following tracheal resection and reconstruction, requiring different treatment strategies for simultaneous PTS. We present a patient suffering from end-stage heart failure and post-intubation tracheal stenosis along with our treatment strategy.
Keywords: heart; trachea; post-intubation tracheal stenosis; heart transplantation